Room‐Temperature, Strain‐Tunable Orientation of Magnetization in a Hybrid Ferromagnetic Co Nanorod–Liquid Crystalline Elastomer Nanocomposite. Issue 37 (17th July 2015) - Riou, Ophélie; Lonetti, Barbara; Tan, Reasmey P.; Harmel, Justine; Soulantica, Katerina; Davidson, Patrick; Mingotaud, Anne‐Françoise; Respaud, Marc; Chaudret, Bruno; Mauzac, Monique
Abstract Hybrid nanocomposites based on magnetic nanoparticles dispersed in liquid crystalline elastomers are fascinating emerging materials. Their expected strong magneto‐elastic coupling may open new applications as actuators, magnetic switches, and for reversible storage of magnetic information. We report here the synthesis of a novel hybrid ferromagnetic liquid crystalline elastomer. In this material, highly anisotropic Co nanorods are aligned through a cross‐linking process performed in the presence of an external magnetic field. We obtain a highly anisotropic magnetic material which exhibits remarkable magneto‐elastic coupling. The nanorod alignment can be switched at will at room temperature by weak mechanical stress, leading to a change of more than 50 % of the remnant magnetization ratio and of the coercive field.